Analisa Waste Man hours Pada Pekerjaan Modifikiasi Structure Bulkhead Body STA 2598 Pesawat 747-400 Di PT. GMF Aeroasia Tbk - Sutaarga, Ossa; Syarief, Ivan Andrian (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2023)
This study aims to determine the cause of the actual man hours that did not reach the target in the interim modification work which refers to the modification of the STA 2598 bulkhead body structure on the 747-400 aircraft at PT. GMF Aeroasia Tbk. Tangerang. The type of research used in this study is a qualitative and quantitative method which refers to data taken from 15 aircraft that have performed aircraft maintenance at PT. GMF Aeroasia Tbk. By analyzing the man hours that have been partnered with the SAP application, value stream mapping analysis techniques are obtained to find out the source of the problem from the man hours delay with the stages of making current state mapping in current conditions, making process activity mapping to map existing activities at the time of work. takes place based on VA, NVA and NNVA and obtained from the results of the study the biggest cause of out of target in manhours in the modification of the structure of the bulkhead body STA 2598 on the 747-400 aircraft that was treated at PT. GMF AeroAsia Tbk is waste over processing which reaches 21 hours 38 minutes with a percentage of 14.74%, waste waiting as much as 1 hour 14 minutes with a percentage of 0.84% and a total waste motion of 30 minutes with a percentage of 0.34% with a total waste during work lasted for 23 hours 22 minutes with a percentage of 15, 97% with the proposed improvement by increasing the effectiveness of duration manhours which previously reached 145 hours 4 minutes, to 121 hours 12 minutes. Keywords: VSM, Maintenance, Waste Analysis, Manhours, PAM